Teaching Strategies and Activities that Encourage Students of I Cycle at Colegio Católica Nuestra Señora de Guadalupe into Communicating in English - Azofeifa Arias, Patricia (P. Azofeifa A., 2017)
The present educational study intends to research strategies and activities that encourage students to communicate in English. Speaking a language other than the native tongue not only allows children to communicate with a vast number of people, but it also affects their cognitive development positively, and this is something they can benefit from throughout their lives. Therefore, this study seeks to answer the question: "Which are the teaching strategies and activities that prompt students into communicating in English in the classroom?" The research was developed at Colegio Católico Nuestra Señora de Guadalupe; the subjects chosen from this study were the first cycle students. A total of nine non-participant observations were carried out, three for each level in order to identify the students´ performance during the English class; questionnaires for the students and interviews to the teachers were also applied. The study contains two categories: methodology and performance, and six subcategories: learning strategies, teaching techniques, didactic resources, class environment, productive skills and receptive skills.